2022
DOI: 10.3390/diagnostics12061445
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Deep Learning System for Automatic Diagnosis of Protruding Lesions in Colon Capsule Endoscopy

Abstract: Background: Colon capsule endoscopy (CCE) is an alternative for patients unwilling or with contraindications for conventional colonoscopy. Colorectal cancer screening may benefit greatly from widespread acceptance of a non-invasive tool such as CCE. However, reviewing CCE exams is a time-consuming process, with risk of overlooking important lesions. We aimed to develop an artificial intelligence (AI) algorithm using a convolutional neural network (CNN) architecture for automatic detection of colonic protruding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To date, this has been mainly tested for the small bowel[ 69 , 70 ], while it remains scarcely explored in the case of double-headed capsules. A few studies of CNN development for CC endoscopy revealed a very high accuracy for detection of colorectal neoplasia or protruding lesions[ 71 - 73 ]. Mascarenhas et al [ 74 ] recently developed a CNN for automatic detection of colonic blood in CC endoscopy, enabling the differentiation between normal mucosa, blood or hematic residues and pleomorphic mucosal lesions, namely ulcers and erosions, protruding lesions and vascular lesions.…”
Section: Ai In Cementioning
confidence: 99%
“…To date, this has been mainly tested for the small bowel[ 69 , 70 ], while it remains scarcely explored in the case of double-headed capsules. A few studies of CNN development for CC endoscopy revealed a very high accuracy for detection of colorectal neoplasia or protruding lesions[ 71 - 73 ]. Mascarenhas et al [ 74 ] recently developed a CNN for automatic detection of colonic blood in CC endoscopy, enabling the differentiation between normal mucosa, blood or hematic residues and pleomorphic mucosal lesions, namely ulcers and erosions, protruding lesions and vascular lesions.…”
Section: Ai In Cementioning
confidence: 99%
“…Deep learning was integrated into the field with the study by Yuan and Meng in 2017 [62] , where they utilised a stacked sparse autoencoder method to categorise images into polyps, bubbles, turbid images, and clear images with an overall accuracy of 98.00%. Since then, 12 deep learning applications were used for polyp and tumour detection [63][64][65][66][67][68][69][70][71][72][73][74] . More recently, a study by Lafraxo et al in 2023 proposed an innovative model using CNN (Resnet50), where they achieved an accuracy of 99.16% on the MICCAI 2017 WCE dataset [73] .…”
Section: Polyps and Tumoursmentioning
confidence: 99%
“…AI in colon capsule endoscopy is a new field of interest. Recently, Afonso et al [ 26 ] analysed 24 CCE exams (PillCam ® COLON 2) performed at a single centre between 2010 and 2020. From these video recordings, 3635 frames of the colonic mucosa were extracted, 770 containing colonic ulcers or erosions and 2865 showing normal colonic mucosa.…”
Section: Evidence-based Literature Review Of Ai and Ccementioning
confidence: 99%
“… Study No. of Images Colonic Lesion Normal Colonic Mucosa Sensitivity Specificity Accuracy of the Network AUROC for Detection of Protruding Lesion Afonso [ 26 ] 3635 770 2865 90.3% 98.8% 97.0% 0.99 Saraiva [ 2 ] 5715 2410 3305 90.0% 99.1% 95.3% 0.99 Atsuo Yamada [ 27 ] 4784 1850 2934 79.0% 87.0% 0.902 Hiroaki Saito [ 28 ] 17,507 7507 10,000 90.0% 79.0% 0.911 Nadimi, E.S [ 14 ] 1695 4800 6500 …”
Section: Table A1mentioning
confidence: 99%